Classification of partial seizures based on functional connectivity: A MEG study with support vector machine - Wang, Yingwei; Li, Zhongjie; Zhang, Yujin; Long, Yingming; Xie, Xinyan; Wu, Ting (Frontiers in Neuroinformatics, 2022)
Temporal lobe epilepsy (TLE) was a chronic neurological disorder that was divided into two subtypes, complex partial seizures (CPS) and simple partial seizures (SPS), based on clinical phenotypes. Revealing differences among the functional networks of different types of TLE can lead to a better understanding of the symbology of epilepsy. Whereas most studies had focused on differences between epileptic patients and healthy controls, the neural mechanisms behind the differences in clinical representations of CPS and SPS were unclear. In the context of the ear of precision medicine makes precise classification of CPS and SPS crucial. To address the above issues, we aimed to investigate the functional network differences between CPS and SPS by constructing support vector machine (SVM) models. It mainly includes: magnetoencephalography (MEG) data acquisition and processing, construction of functional connectivity matrix of brain network, and the use of SVM to identify differences in resting state functional connectivity (RSFC). The obtained results showed that classification was effective and accuracy could be up to 82.69% (training) and 81.37% (test). The differences in functional connectivity between CPS and SPS were smaller in temporal and insula. The differences between the two groups were concentrated in the parietal, occipital, frontal and limbic systems. Loss of consciousness and behavioral disturbances in CPS patients might be caused by abnormal functional connectivity in extratemporal regions produced by post-epileptic discharges. This study not only contributed to understanding of the cognitive-behavioral comorbidity of epilepsy, but also improved the accuracy of epilepsy classification.